Spray nozzles and droplet size effects on soybean canopy deposits and stink bugs control in west region of Sao Paulo state-Brazil - Farias, Matheus A. G. L. [UNESP]; Raetano, Carlos G. [UNESP]; Chechetto, Rodolfo G. [UNESP]; Ferreira-Filho, Pedro J.; Guerreiro, Julio C.; Bonini, Carolina S. B. [UNESP]; Firmino, Ana C. [UNESP]; Lima, Ronaldo C. [UNESP]; Prado, Evandro P. [UNESP] (Springer, 2020)
Stink bugs are one of the most relevant pest affecting soybean yields beyond the physiological and sanitary quality of the soybean seeds. The aim of the present study was to evaluate the effect of spray nozzles and droplet size on spray deposits into soybean canopy and the biological efficacy of insecticide used to control stink bugs. Field experiments were conducted at the Sao Paulo State University, Brazil, comparing the effects of spray nozzles: hollow cone TXA 8002 VK (very fine droplet), extended range flat fan XR 8003 (fine/medium droplet), twin flat fan TTJ 6011002 (medium droplet), air induction flat fan AIXR 110025 (very/extremely coarse droplet) and drift guard twin flat fan DGTJ 11002 (fine droplet) using for all treatments an application rate of 218 L ha(-1). Spray deposits on soybean leaves taken from the bottom, middle and top canopy tiers were quantified with insecticide associated with Brilliant Blue dye. In general, the amount of spray deposits on soybean canopy had little difference regardless the spray nozzle type. The mortality of stink bugs shows no significant difference regardless the spray nozzle type on the treatments applied insecticide. The stink bugs provide reduction on soybean yield on the treatment only without insecticide application.
Keywords: Application technology; Insecticide; Spray deposition; Piezodorus guildinii